Analisis Kadar Kalsium (Ca) dan Posforus (P) pada Buah Pare (Momordica charantia L) dari Boyaoge dan Sidera Palu Sulawesi Tengah - Diniyanti, Diniyanti; Nuryanti, Siti; Said, Irwan (Universitas Tadulako, 2018)
The aim of this study was to determine calcium (Ca) and phosphorus (P) levels in pare (Momordica charantia L) fruits. Samples were obtained from Boyaoge and Sidera Palu, Central Sulawesi. Analyzing calcium (Ca) and phosphorus (P) levels in pare used the Spectrodirect instrument. The analysis results obtained the average concentration values of the calcium in the samples of pare from Boyaoge and Sidera were 6.0 mg/L and 8.3 mg/L, respectively, while the average concentration values of the phosphorus in the samples were 4.3 mg/L and 6.5 mg/L, respectively. These results showed that the higher concentration of calcium (Ca) and phosphorus (P) in pare fruit was obtained from Sidera.